Nursing Care with A Medical Diagnosis of Non-hemorrhagic Stroke in High Care Unit of Banjarnegara Islamic Hospital: A Case Study - Latifah; Mamat Setiawan; Adiratna Sekar Siwi (Genius Journal, 2022)
Objective: The purpose of this study was to determine the development of non-hemorrhagic stroke patients by maximizing the implementation of ROM during treatment. Method: The method used is descriptive method with a case study approach in non-haemorrhagic stroke patients with decreased consciousness. The case study process was carried out by finding patient data and classified according to continued inclusion criteria. interviews (to the family) and secondary data collection from medical records, observation of the patient's condition and periodic physical examinations. After obtaining the data, further documentation of the nursing process is carried out from assessment, data analysis, nursing problems, nursing interventions, nursing implementation and evaluation. Result: Nursing problems that arise include: risk of ineffective cerebral perfusion related to hypertension, ineffective airway clearance related to retained secretions and impaired physical mobility associated with decreased muscle strength, Three nursing problems have not been resolved because stroke is a brain tissue damage that is characterized by irreversible (cannot be returned) and it takes a long time for the recovery process.